2021
DOI: 10.1101/2021.03.15.435430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Echolocation reverses information flow in a cortical vocalization network

Abstract: The mammalian frontal and auditory cortices are fundamental structures supporting vocal production, yet the dynamics of information exchange between these regions during vocalization are unknown. Here, we tackle this issue by means of electrophysiological recordings in the fronto-auditory network of freely-vocalizing Carollia perspicillata bats. We find that oscillations in frontal and auditory cortices provide correlates of vocal production with complementary patterns across structures. Causality analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 105 publications
(212 reference statements)
0
3
0
Order By: Relevance
“…What might be even more important than the awake state might be the vocalizing state. Despite of recent technological advances, neural recordings from actively echolocating bats have rarely been conducted ( Sinha and Moss, 2007 ; Kothari et al, 2018 ; Weineck et al, 2020 ; García-Rosales et al, 2022 ). However, it is indisputable that attentional effects occurring during active vocalization may completely alter neural processing of echolocation signals.…”
Section: Neural Recordings From Awake and Echolocating Batsmentioning
confidence: 99%
See 2 more Smart Citations
“…What might be even more important than the awake state might be the vocalizing state. Despite of recent technological advances, neural recordings from actively echolocating bats have rarely been conducted ( Sinha and Moss, 2007 ; Kothari et al, 2018 ; Weineck et al, 2020 ; García-Rosales et al, 2022 ). However, it is indisputable that attentional effects occurring during active vocalization may completely alter neural processing of echolocation signals.…”
Section: Neural Recordings From Awake and Echolocating Batsmentioning
confidence: 99%
“…The same study showed that frontal areas, which are likely involved in vocalization initiation, couple their activity with sensory-motor structures such as the striatum after echolocation ( Weineck et al, 2020 ). In addition, information flows between frontal and auditory cortices reverses directionality after bats echolocate ( García-Rosales et al, 2022 ) indicating that the results could be completely different in vocalizing compared to non-vocalizing bats.…”
Section: Neural Recordings From Awake and Echolocating Batsmentioning
confidence: 99%
See 1 more Smart Citation